2011
DOI: 10.1111/j.1399-3046.2010.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary HHV 6 infection after liver transplantation with acute graft rejection and multi‐organ failure: Successful treatment with a 2.5‐fold dose of cidofovir and reduction of immunosuppression

Abstract: HHV type 6 has been reported with enhanced pathogenicity in immunocompromised patients. Herein, we report about a two-yr-old girl who experienced primary HHV 6 infection after liver transplantation. She clinically presented with graft rejection and necrotic hepatitis as well as high fever, pneumonitis with respiratory failure and a rash. Therapy with cidofovir of 5 mg/kg per wk did not show improvement, so that a full pharmacokinetic profile of cidofovir was performed. It demonstrated enhanced body weight norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Patients with clinically significant HHV-6 infection after liver transplantation commonly present with unexplained fever. 8,24,25 Among adult transplant patients with HHV-6 plasma viraemia, five (29.4%) of 17 presented with unexplained fever at the time of reactivation. 8 Fever may be associated with skin rash, 25,26 myelosuppression 27 or elevated transaminases.…”
Section: Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with clinically significant HHV-6 infection after liver transplantation commonly present with unexplained fever. 8,24,25 Among adult transplant patients with HHV-6 plasma viraemia, five (29.4%) of 17 presented with unexplained fever at the time of reactivation. 8 Fever may be associated with skin rash, 25,26 myelosuppression 27 or elevated transaminases.…”
Section: Fevermentioning
confidence: 99%
“…8,24,25 Among adult transplant patients with HHV-6 plasma viraemia, five (29.4%) of 17 presented with unexplained fever at the time of reactivation. 8 Fever may be associated with skin rash, 25,26 myelosuppression 27 or elevated transaminases. [28][29][30]…”
Section: Fevermentioning
confidence: 99%
“…Allograft dysfunction and rejection is gaining more traction as a serious complication of HHV-6B reactivation [44] or primary infection [45], particularly in liver transplantation. Retrospective testing for HHV-6 DNA in 26 liver biopsies was positive in 39% of patients with graft hepatitis of unclear etiology, and confluent periportal necrosis was associated with high viral loads in 4 patients who responded to antiviral therapy [46].…”
Section: Human Herpesvirus 6bmentioning
confidence: 99%
“…HHV‐6 infection of transplanted livers may cause increased adhesion molecule expression on vascular endothelial cells resulting in lymphocyte infiltration . Primary infection with HHV‐6 in infants after liver transplantation has been associated with hepatitis and graft rejection . A prospective study in liver transplant patients concluded that HHV‐6 detection in serum by PCR is independently correlated with biopsy‐proven graft rejection .…”
Section: Discussionmentioning
confidence: 99%